Life support technology of beach glamping using renewable energy of sea waves - V. V. Mironov; Yu. A. Ivanyushin; D. A. Suglobov; D. V. Mironov; L. I. Maksimov (Vestnik MGSU)
Introduction. The growth of domestic tourism in the Russian Federation is forecasted to reach 30 % by the end of 2023 compared to the results of 2022. At the same time, ecological tourism in areas with undeveloped engineering infrastructure has become one of the trends of recent years.Materials and methods. To solve the problems of life support of temporary accommodation facilities (glamping), a technical solution for the conversion of hydraulic wave energy in the coastal zone of Russian sea areas is proposed. The purpose of the research is a feasibility study of the application of innovative life support technology based on renewable wave energy to provide municipal resources, including fresh water, to non-permanent accommodation facilities (beach glamping). To achieve this goal, numerical research methods were used using statistical data and long-term observational data, searching for domestic and foreign sources with analysis and comparison of the contained data.Results. Calculations of fresh water productivity are presented, taking into account the unevenness of wave characteristics (heights, periods) throughout the year using the example of the Black sea and the Sea of Japan. It is established that even taking into account the uneven wave characteristics, the Black Sea coastal zone is a commercially significant territory for implementation. The coastal zone of the Sea of Japan is a promising territory in the case of seasonal operation of facilities with the proposed technology. The payback period of the technology for operation on the Black Sea coast was determined.Conclusions. The proposed pump-compressor is able to replace energy-consuming equipment of reverse osmosis installations — high-pressure pumps for supplying seawater to the membranes. The use of technology on the freezing seas is expedient in the non-year-round operation mode. The payback period, depending on the cost of electricity, does not exceed two years without taking into account the associated removal of useful pneumatic power.